(3SjchdhLjI Gdaf(B/ s - (3eGPQ, LhQLs ((3GdbGgQI, s (3GdeMQhSI, s, 2023)
"Psychology of Art" provides a broad introduction to how psychology helps us understand and appreciate creative activities. It explores the influence of perception on art throughout history, highlighting its role as a constant source of inspiration, conflict, and debate. The book also examines factors like forgery and sexual bias in shaping our judgments about art. By questioning the link between psychology and art appreciation, it offers fresh insights into the creation and consumption of art.
(3jbOe dfG cJGH (B"(3SjocdhLjI Gdaf(B" (3neONkdG JhajbkqjG Edi GdWQGFb GdeJfhYI GdJj jecf dYde GdfaS Cf jSGYnOfG HgG aj age GdCfTWI GdEHOGYjI hJbOjpQgG(B. (3hNdGnd GSJcTGpa GdcJGpH cjajnI EOQGpcfG ocnqd TjmA ef Gddhf Edi GdMQcI, njaMoU UfGYnI Gdaqf HnhUpagG TckdG ef CTcGd GdSdhc GdEfSGfj jeJqO YHQ GdJGQjN eUOkQG eJLOkOG ddEdgGe hGdUQGY hGdpqfbGT(B. (3ceG jfXQ GdpcJGH HnYjf GdGYJHGQ Edi JCKjpQ YhGend cGdJRjjpa hJbfjI GdnqfSN hGdJMoqjR GdLfSqj Ydi CMcGpefG HTCf Gdaf(B. (3hef NdGd JSGDd GdpcJGH Yf WHjYI GdYdGbI Hjf Yde GdfaS hJbOjQ Gdaqf jbqOe ddbGQF WQGFnb LOjOkI ddJacjQ aj GdcjajI GdJj nfNdob HgG Gdaqf hfSJgdocg(B.s
Title translation: Psychology of art- Author: George Madhr
Arabic
Keywords: N61-72 Study and Teaching. Research